Independence Of Abby Reflected In Let Me In Movie 2010 Directed By Matt Reeves A Feminist Approach - Purwasih, Yuni, Dr. Phil. DewiCandraningrum, S.Pd., M.Ed, Titis Setyabudi, S.S., M. Hum (2013)
The major issue of this study is how the independence of Abby is reflected in Let Me In movie 2010 by Matt Reeves based on a feminist perspective. The objective of this study is to analyze the movie in terms of its structural elements and to analyze the Let Me In movie based on the feminist perspective. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The secondary data are taken from several references such as articles, website about the movie, commentaries, and other about the author on feminism material to support the subject matter. The data collection method is library research by collecting both primary and secondary data. The data analysis method is descriptive qualitative analysis based on feminism approach. The results of the study show; firstly, Matt Reeves wants to illustrate how women are subordinated and exploited in patriarchal society. Secondly, in this Let Me In movie, it can be seen from Abby's condition where she always struggles to keep her relationship and also her love on Owen. Thirdly, in this Let Me Inmovie, Abby tries to follow every Owen's activity.